Phosphate adsorption on aluminum-impregnated mesoporous silicates: surface and behavior of adsorbents - Eun, Woo Shin; Han, James S.; Min, Jang; Soo, Hong Min; Jae, Kwang Park; Rowell, Roger M. (American Chemical Society, 2008)
Phosphorus from excess fertilizers and detergents ends up washing into lakes, creeks, and rivers. This overabundance of phosphorus causes excessive aquatic plant and algae growth and depletes the dissolved oxygen supply in the water. In this study, aluminum-impregnated mesoporous adsorbents were tested for their ability to remove phosphate from water. The surface structure of the materials was investigated with X-ray diffraction (XRD), a N2 adsorption-desorption technique, Fourier transform-infrared (FT-IR), and X-ray photoelectron spectroscopy (XPS) to understand the effect of surface properties on the adsorption behavior of phosphate. The mesoporous materials were loaded with Al components by reaction with surface silanol groups. In the adsorption test, the Al-impregnated mesoporous materials showed fast adsorption kinetics as well as high adsorption capacities, compared with activated alumina. The uniform mesopores of the Al-impregnated mesoporous materials caused the diffusion rate in the adsorption process to increase, which in turn caused the fast adsorption kinetics. High phosphate adsorption capacities of the Alimpregnated mesoporous materials were attributed to not only the increase of surface hydroxyl density on Al oxide due to well-dispersed impregnation of Al components but also the decrease in stoichiometry of surface hydroxyl ions to phosphate by the formation of monodentate surface complexes.